Stromal heparan sulfate differentiates neuroblasts to suppress neuroblastoma growth - Erik H. Knelson; Angela L. Gaviglio; Jasmine C. Nee; Mark D. Starr; Andrew B. Nixon; Stephen G. Marcus; Gerard C. Blobe (The Journal of Clinical Investigation, 2014)
Neuroblastoma prognosis is dependent on both the differentiation state and stromal content of the tumor. Neuroblastoma tumor stroma is thought to suppress neuroblast growth via release of soluble differentiating factors. Here, we identified critical growth-limiting components of the differentiating stroma secretome and designed a potential therapeutic strategy based on their central mechanism of action. We demonstrated that expression of heparan sulfate proteoglycans (HSPGs), including TβRIII, GPC1, GPC3, SDC3, and SDC4, is low in neuroblasts and high in the Schwannian stroma. Evaluation of neuroblastoma patient microarray data revealed an association between TGFBR3, GPC1, and SDC3 expression and improved prognosis. Treatment of neuroblastoma cell lines with soluble HSPGs promoted neuroblast differentiation via FGFR1 and ERK phosphorylation, leading to upregulation of the transcription factor inhibitor of DNA binding 1 (ID1). HSPGs also enhanced FGF2-dependent differentiation, and the anticoagulant heparin had a similar effect, leading to decreased neuroblast proliferation. Dissection of individual sulfation sites identified 2-O, 3-O-desulfated heparin (ODSH) as a differentiating agent, and treatment of orthotopic xenograft models with ODSH suppressed tumor growth and metastasis without anticoagulation. These studies support heparan sulfate signaling intermediates as prognostic and therapeutic neuroblastoma biomarkers and demonstrate that tumor stroma biology can inform the design of targeted molecular therapeutics.